Targeting CDK5 in Astrocytes Promotes Calcium Homeostasis Under Excitotoxic Conditions - Toro-Fernández, Luisa Fernanda; Zuluaga-Monares, Juan Camilo; Saldarriaga-Cartagena, Ana María; Cardona-Gómez, Gloria Patricia; Posada-Duque, Rafael (Frontiers in Cellular Neuroscience, 2021)
Glutamate excitotoxicity triggers overactivation of CDK5 and increases calcium influx in neural cells, which promotes dendritic retraction, spine loss, increased mitochondrial calcium from the endoplasmic reticulum, and neuronal death. Our previous studies showed that CDK5 knockdown (KD) in astrocytes improves neurovascular integrity and cognitive functions and exerts neuroprotective effects. However, how CDK5-targeted astrocytes affect calcium regulation and whether this phenomenon is associated with changes in neuronal plasticity have not yet been analyzed. In this study, CDK5 KD astrocytes transplanted in CA3 remained at the injection site without proliferation, regulated calcium in the CA1 hippocampal region after excitotoxicity by glutamate in ex vivo hippocampal slices, improving synapsin and PSD95 clustering. These CDK5 KD astrocytes induced astrocyte stellation and neuroprotection after excitotoxicity induced by glutamate in vitro. Also, these effects were supported by CDK5 inhibition (CDK5i) in vitro through intracellular stabilization of calcium levels in astrocytes. Additionally, these cells in cocultures restored calcium homeostasis in neurons, redistributing calcium from somas to dendrites, accompanied by dendrite branching, higher dendritic spines and synapsin-PSD95 clustering. In summary, induction of calcium homeostasis at the CA1 hippocampal area by CDK5 KD astrocytes transplanted in the CA3 area highlights the role of astrocytes as a cell therapy target due to CDK5-KD astrocyte-mediated synaptic clustering, calcium spreading regulation between both areas, and recovery of the intracellular astrocyte-neuron calcium imbalance and plasticity impairment generated by glutamate excitotoxicity.